2006
DOI: 10.1111/j.1462-2920.2006.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Coselection for microbial resistance to metals and antibiotics in freshwater microcosms

Abstract: Bacterial resistances to diverse metals and antibiotics are often genetically linked, suggesting that exposure to toxic metals may select for strains resistant to antibiotics and vice versa. To test the hypothesis that resistances to metals and antibiotics are coselected for in environmental microbial assemblages, we investigated the frequency of diverse resistances in freshwater microcosms amended with Cd, Ni, ampicillin or tetracycline. We found that all four toxicants significantly increased the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
146
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(160 citation statements)
references
References 18 publications
14
146
0
Order By: Relevance
“…The second is that other selective pressures play a role in inducing FQ r bacteria. This is supported by findings that some heavy metals cause drugresistance in bacteria (2,54). A combination of the two possibilities may also apply.…”
Section: Discussionsupporting
confidence: 63%
“…The second is that other selective pressures play a role in inducing FQ r bacteria. This is supported by findings that some heavy metals cause drugresistance in bacteria (2,54). A combination of the two possibilities may also apply.…”
Section: Discussionsupporting
confidence: 63%
“…In the case of TC resistance, it is known that treatment with a single drug leads to resistance of that drug and cross-resistance to other drugs 4) . Furthermore, a recent study reported that resistance to metals and TC are linked 16) . In our study, chemicals other than TC/OTC or TBT might have presented selective pressure to environmental bacteria, which may have resulted in cross-resistance to TC as well as to TBT.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, indirect selection may also be made, because some TMMR are present in genetic structures that also include other antibiotic resistance determinants such as dfrA genes, involved in resistance to trimethoprim, aacA or aadA genes, involved in aminoglycoside resistance or b-lactamase genes, involved in b-lactam resistance, among others (Dolejska et al, 2013;Du et al, 2012;Ho et al, 2011;Pons et al, 2015;S aenz et al, 2010). Thus, the TMMR may be fixed in the bacterial genetic background by the use of unrelated antimicrobial agents, or by the presence of heavy metals or antibiotic traces in the environment as has been described in other cases (Stepanauskas et al, 2006;Vien et al, 2012).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%